Cognitive failure and driving distraction on private car drivers using naturalistic driving study - Al Baihaqi, Hasby; Lady, Lovely (Universitas Sultan Ageng Tirtayasa, 2024)
Driving requires the driver to have physical and cognitive readiness. Cognitive failure can impact driving performance and lead to accidents. This study aims to identify factors that cause cognitive failure, determine the average score of cognitive failure in private car drivers, and identify distractions frequently experienced by drivers during driving. For data collection, the observer rode as a passenger in the respondent's car and identified driving distractions using a checklist. Cognitive failure rates were measured using the Cognitive Failure Questionnaire (CFQ). The distribution of questionnaires to drivers occurred after naturalistic driving. The research found that driver cognitive failure is at a high to moderate level, with distractibility being the dominant factor. The distractions experienced were predominantly internal. The adolescent group experienced more driving distractions than the adult group.